A qualitative study of stigma among disabled elders with stroke and their primary caregivers (脑卒中失能老人及其主要照顾者病耻感的质性研究) - KE Ke (柯珂); HE Juanfeng (贺娟凤); WANG Wei (汪维) (中西医结合护理)
Objective To investigate the experience of stigma among disabled elders with stroke and their primary caregivers, analyze potential reasons and measures to relieve the feeling of stigma, and provide a reference for medical workers to carry out targeted psychological care and comprehensive interventions. Methods Phenomenological research design and semi-structural interviews were conducted on 13 disabled elders with stroke and their primary caregivers, and the collected data were analyzed with the method of Colaizzi Phenomenological analysis. Results By analyzing and sorting out the data, 3 themes and 9 sub-themes related to the experience of stigma were put forward: cognitive attribution (label recognition, abnormal behavior, attitudes of others, lack of social support), negative emotional response (guilt and remorse, anomaly discrimination, belief in suicide) and non-adaptive coping style (social withdrawal, conceal illness). Conclusion Research findings had identified varying degrees of stigma among disabled elders with stroke and their primary caregivers. Medical and social workers should pay more attention on experience of stigma among disabled elders with stroke and their primary caregivers. More efforts should be made to improve patients and their caregivers’ mental resilience and positive coping skills, and improve the recovery of physical and psychosocial function among patients and their caregivers. (目的 了解脑卒中失能老人及其主要照顾者病耻感的真实内心体验, 探讨其原因并寻求减轻或消除疾病带来的病耻感的方法, 以期为医护人员制定有针对性的心理护理和全面有效的干预措施提供理论依据。方法 2020年6月—12月, 采用目的抽样法选取武汉市某三甲医院老年科住院的脑卒中患者及其主要照顾者作为研究对象, 运用质性研究中的现象学研究方法, 进行半结构式访谈, 采用主题分析法对资料进行分析。结果 提炼出3个主题, 9个副主题, 分别是认知归因(标签认可、行为异常、他人态度、社会支持缺乏)、负性情绪反应(自责与内疚、感知异常歧视、自杀信念)、非适应性行为应对(回避社交、隐瞒病情)。结论 脑卒中失能老人及其主要照顾者存在不同程度的病耻感。医护人员和社会工作者应高度重视脑卒中失能老人及其主要照顾者病耻感的问题, 深入了解脑卒中失能老人及其主要照顾者内心的真实感受, 积极帮助该人群进行机体重建, 提高其心理弹性, 指导其建立积极的应对方式, 促进脑卒中失能老人及其主要照顾者生理和心理社会功能的恢复。)